PKCα regulates the hypertrophic growth of cardiomyocytes through extracellular signal–regulated kinase1/2 (ERK1/2) - Braz, Julian C. (The Rockefeller University Press, 2002)
Members of the protein kinase C (PKC) isozyme family are important signal transducers in virtually every mammalian cell type. Within the heart, PKC isozymes are thought to participate in a signaling network that programs developmental and pathological cardiomyocyte hypertrophic growth. To investigate the function of PKC signaling in regulating cardiomyocyte growth, adenoviral-mediated gene transfer of wild-type and dominant negative mutants of PKCα, βII, δ, and ɛ (only wild-type ζ) was performed in cultured neonatal rat cardiomyocytes. Overexpression of wild-type PKCα, βII, δ, and ɛ revealed distinct subcellular localizations upon activation suggesting unique functions of each isozyme in cardiomyocytes. Indeed, overexpression of wild-type PKCα, but not βII, δ, ɛ, or ζ induced hypertrophic growth of cardiomyocytes characterized by increased cell surface area, increased [(3)H]-leucine incorporation, and increased expression of the hypertrophic marker gene atrial natriuretic factor. In contrast, expression of dominant negative PKCα, βII, δ, and ɛ revealed a necessary role for PKCα as a mediator of agonist-induced cardiomyocyte hypertrophy, whereas dominant negative PKCɛ reduced cellular viability. A mechanism whereby PKCα might regulate hypertrophy was suggested by the observations that wild-type PKCα induced extracellular signal–regulated kinase1/2 (ERK1/2), that dominant negative PKCα inhibited PMA-induced ERK1/2 activation, and that dominant negative MEK1 (up-stream of ERK1/2) inhibited wild-type PKCα–induced hypertrophic growth. These results implicate PKCα as a necessary mediator of cardiomyocyte hypertrophic growth, in part, through a ERK1/2-dependent signaling pathway.